2017
DOI: 10.1038/modpathol.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Mutually exclusive recurrent KRAS and MAP2K1 mutations in Rosai–Dorfman disease

Abstract: Rosai-Dorfman disease is a histiocytic disorder with a poorly-defined pathogenesis. Recent molecular studies have revealed recurrent mutations involving genes in the MAPK/ERK pathway in Langerhans cell histiocytosis and Erdheim-Chester disease. However, cases of Rosai-Dorfman disease have rarely been assessed. We performed next-generation sequencing to assess 134 genes on 21 cases of Rosai-Dorfman disease, including 13 women and 8 men with a median age of 43 years (range, 3–82). Thirteen had extranodal, 5 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
134
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(140 citation statements)
references
References 49 publications
4
134
0
2
Order By: Relevance
“…Case 1 carried five distinct mutations, three of which involve the MAPK pathway (Table ). Identical mutations in MAP2K1 have been reported in two cases of LCH, with a different mutation at the same residue (c.157T>G p.F53V) previously reported in a single case of RDD (Brown et al , ; Garces et al , ). Nonsense mutations are among the most common types of disease‐associated mutation involving NF1 , with mutations occurring around codon 1152 known to be pathogenic (Ars et al , ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Case 1 carried five distinct mutations, three of which involve the MAPK pathway (Table ). Identical mutations in MAP2K1 have been reported in two cases of LCH, with a different mutation at the same residue (c.157T>G p.F53V) previously reported in a single case of RDD (Brown et al , ; Garces et al , ). Nonsense mutations are among the most common types of disease‐associated mutation involving NF1 , with mutations occurring around codon 1152 known to be pathogenic (Ars et al , ).…”
Section: Discussionmentioning
confidence: 69%
“…This exact variant is a known driver mutation in human colorectal carcinoma (Edkins et al , ). A different mutation at the same residue (c.436G>A, p.A146T) was previously reported in a single case of RDD (Garces et al , ). Case 4 harboured a KRAS c.182A>G p.Q61R mutation (AF = 17%).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Histocytic disorders such as Erdheim‐Chester disease have also shown stabilization with sirolimus therapy . Recent studies have identified KRAS , MAP2K1 , NRAS , and ARAF mutations in patients with RDD, thus implicating a complex pathophysiology, and thus making various targeted therapies for RDD possible …”
mentioning
confidence: 99%
“…O'Malley et al have recently evaluated clonal abnormalities and genetic gains and/or losses in LCH and RDD coexistence, and highlight that these diseases may belong to a spectrum linked by clonal abnormalities 19. Mutually exclusive KRAS and MAP2K1 mutations have been detected in approximately one-third of RDD cases, suggesting MAPK/ERK pathway activation and clonal origin 23. Recently, Ozkaya et al describe the same MAP2K1 mutation detected in a RDD-like testis lesion and Erdheim-Chester disease-like tongue lesion of a patient with known…”
mentioning
confidence: 99%